Human Health Risk Assessment due to Heavy Metals in Ground and Surface Water and Association of Diseases With Drinking Water Sources: A Study From Maharashtra, India - Govind Mawari; Naresh Kumar; Sayan Sarkar; Arthur L Frank; Mradul Kumar Daga; Mongjam Meghachandra Singh; Tushar Kant Joshi; Ishwar Singh (SAGE Publishing, 2022)
Background: Contamination of freshwater sources can be caused by both anthropogenic and natural processes. According to Central Pollution Control Board, Maharashtra along with 2 other states, contribute 80% of hazardous waste generated in India, including heavy metal pollution. Hence, it is important to quantify heavy metal concentrations in drinking water sources in such areas. Materials and methods: Water samples were analyzed for toxic elements (F, As, Cd, Hg, Pb, Ni, Cu, Zn, Mn, and Cr) using Inductively Coupled Plasma-Mass Spectrometry (ICP-MS) Agilent 7500. Health risks due to ingestion and dermal contact was assessed. A total of 557 people were randomly selected, with consumers from all 4 types of water sources that is surface water, hand pump, wells, and municipal water. Spot urine samples were collected from 47 people after considering inclusion and exclusion criteria. Urine was collected for estimating mercury and arsenic levels in the study participants. Results: Arsenic contributes the most health risk from ingestion from water. Among surface water users, 14 people (32%) reported frequent loose stool ( P -value < .05) (OR 2.5), and 11 people (23%) reported frequent abdominal pain (OR 1.9). Hand pump and well water users reported frequent abdominal pain (27%) (OR 1.4) and gastric discomfort (31%) ( P -value < .05) (OR 3) respectively. The mean value of urinary Hg and As were 4.91 ± 0.280 and 42.04 ± 2.635 µg/L respectively. Conclusion: Frequent loose stool, gastric discomfort, and frequent abdominal pain were associated with the various sources of drinking water. Urine Hg levels were found higher than the NHANES (USA) Survey. It is recommended that frequent monitoring of drinking water should be enforced around the industrial hub, so that appropriate actions can be taken if present in excess.